Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Minat Beli Ulang Smartphone Samsung Pada Masyarakat Kota Mataram - Sasmita, Aprilia Ayu; Athar, Handry Sudiartha (Postgraduate, University of Mataram, 2024)
This research aims to determine and analyze the Influence of Product Quality and Price Perception on Interest in Repurchasing Samsung Smartphones in the Mataram City Community. Using a sample of 80 respondents who live in Mataram, this research found that product quality has a positive and significant influence on interest in repurchasing Samsung smartphones and price perception has a positive and significant influence on intention to repurchase Samsung Smartphones. These results indicate that product quality and price perception are effective in increasing interest in repurchasing Samsung Smartphones.